Tourists Becoming Involved: The Influence of Pro-Environmental Voluntourism on Destination Image Formation - Weronika Lis; Mirek Dymitrow; Elżbieta Grzelak-Kostulska (Tourism and Hospitality, 2022)
The purpose of this research was to explore the realization of the pro-environmental initiative in the Faroe Islands in which tourists were involved as volunteers. The research was aimed at understanding how this influences tourists’ perceptions of a destination. We were interested in filling the research gap regarding the importance of tourists’ direct involvement in pro-environmental initiatives in terms of how this experience stimulates their perceptions of a destination image. The quantitative research method was adopted, whereby surveys were conducted among volunteering tourists and regular tourists visiting the Faroe Islands archipelago. The latter group was divided into two subsamples of arriving and departing tourists to understand how their perception changed after the visit. This study challenges the assumptions of the destination image theory, according to which only “accidental” information can affect the organic image of a destination within the mind of a tourist. The study reveals that tourists who tangibly experience a green marketing initiative have a positive opinion about the destination in terms of environmental protection. The organic image itself can be changed through purposeful action on the part of destination managers. We show the importance of the direct involvement of tourists in a volunteering project that is considered valuable in promoting the destination’s environmental image.